PENGEMBANGAN E-MODUL PADA MATERI BADAN USAHA DALAM PEREKONOMIAN INDONESIA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X IPS 4 SMAN 1 KUTOREJO - Silvi Putri Agustin; Mohamad Arief Rafsanjani (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
Limited learning hours during Covid-19 cause students to not be optimal in receiving learning materials at school, so effective teaching materials are needed. The purpose of this research is to develop teaching materials for E-module applications, determine the feasibility of E-modules, the practicality of E-modules and determine the effectiveness of E-modules. This study uses the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The limited experiment was carried out in class X IPS 4 at SMAN 1 Kutorejo. The data collection technique uses a validation questionnaire to determine the feasibility of teaching materials and a questionnaire on the practicality of teaching materials and uses student learning outcomes to determine the effectiveness of E-modules to improve student learning outcomes. Based on the analysis and the results obtained, the average value of total validity is 3,7, the category is very valid. The practicality of teaching materials obtained a total average score of 98.8% in the very practical category. The effectiveness of teaching materials to obtain classical completeness result of 84.8% of the total students who get a score of 75 (KKM), then the teaching materials developed can be said to be effective in improving student learning outcomes